Immunological characterization of a recombinant 27-kilodalton antigenic protein from Paracoccidioides brasiliensis. - Ortiz, B L (1996)
We report the expression in Escherichia coli of a 27-kDa antigenic protein from Paracoccidioides brasiliensis. When analyzed by immunoblotting, this recombinant antigenic protein was recognized by antibodies present in the sera of 40 of the 44 paracoccidioidomycosis patients studied. No cross-reactions were observed with sera from patients with other mycoses (histoplasmosis, aspergillosis, cryptococcosis, sporotrichosis, and chromoblastomycosis) or with tuberculosis.